PERANCANGAN DAN IMPLEMENTASI SISTEM OTOMATISASI PEMELIHARAAN TANAMAN HIDROPONIK - Utama, Hadian Satria; Isa, Sani M.; Indragunawan, Arie (TESLA Jurnal Teknik Elektro UNTAR, 2006)
Nowadays automatitation is become a trend, even though people still using manual ways to do agriculture, especially in hydroponics plantation. By using this device, people don’t have to do watering and maturing hydroponics plants again, because the system will do it automatically.